2005
DOI: 10.1007/s00420-005-0606-x
|View full text |Cite
|
Sign up to set email alerts
|

Normal nerve conduction velocity and vibrotactile perception thresholds in computer users

Abstract: We saw no signs of early neural deficits of large sensory fibres in subjects who intensively use computer keyboard equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…The two groups differed in symptom profile. The findings of Murata et al[ 23 ] were in contrast to a recent study by Sandén et al[ 25 ] in which 82 secretaries with a median of 6 hours of daily computer work were compared to 35 nurses with very limited computer work. No statistically significant differences were found in the median nerve conduction velocity or in the vibration threshold between the two groups in t-test analyses.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The two groups differed in symptom profile. The findings of Murata et al[ 23 ] were in contrast to a recent study by Sandén et al[ 25 ] in which 82 secretaries with a median of 6 hours of daily computer work were compared to 35 nurses with very limited computer work. No statistically significant differences were found in the median nerve conduction velocity or in the vibration threshold between the two groups in t-test analyses.…”
Section: Resultsmentioning
confidence: 61%
“…Seven studies comparing median nerve function in computer users with groups without computer use were found [ 19 - 25 ]. Two of the studies assessed median nerve function with NCT [ 23 , 25 ] whereas the other five studies used vibration perception threshold testing. Vibration sense perception, however, is not a good indicator of CTS [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence is linking peripheral nerve dysfunction to conditions with "non-specific" upper limb pain: While some studies found similar nerve conduction velocity and vibrotactile perception in healthy computer users and non-exposed controls [ 20 ] others have demonstrated sub-clinical median nerve impairment [ 21 ] and elevated threshold for perception of vibration [ 17 , 22 ] persisting along with symptoms [ 23 ]. A recent study demonstrated a 15% increased threshold for vibration in computer operators with paraestesiae in contrast to those without paraestesiae [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with those of Murata et al who assessed employees entering data for more than 6 hrs./day, and found significant differences in median sensory conduction velocities 14 . In contrast, Sanden et al reported no statistically significant difference in median nerve conduction velocity 15 . Due to the repetitive movements inherent in computer use, friction is produced, which may lead to the inflammatory changes and resultant nerve compression.…”
Section: Discussion and Resultsmentioning
confidence: 88%